The New Norms of Cosmetic Surgery among Youth in Malaysia - Parveen, Kaur (Cosmos Scholars Publishing House, 2023)
Aesthetics is a complex concept that makes it hard for humans to define beauty. Beauty is a relative term and varies from person to person. The desire to be beautiful is natural among most human beings nowadays. The main objective to conduct this research was to study the views of cosmetic surgery among youth in Malaysia. The specific objectives were to explore the causes that drive youth to undergo cosmetic surgery, to find out the physical and psychological effects on youth who underwent cosmetic surgery and to analyze the acceptance of cosmetic surgery as a common norm and an accepted form of self-improvement. This research focused on youth who underwent cosmetic surgery, between the ages of 15 to 40 years olds in Malaysia. The qualitative method chosen for this research was faceto-face interviews on four respondents using open-ended questions to obtain real data. This study informed about diverse perspectives of beauty which were held by different people from various backgrounds. The factors that influence youth were to enhance their appearance encountering the criticisms from public and to boost their confidence. However, the effects of doing so could be devastating as the risks are unpredictable. It is recommended that future research on this topic may include more respondents of diverse ages especially older men and women to find the extent of the factors.